(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The optimal setting for warp tension in weaving is not a universal constant but a function of the intrinsic properties of the yarn material being processed. This paper investigates the complex relationship between yarn composition (cotton, synthetics, blends), structural mechanics (count, strength, elongation), and the required applied tension. We present methodologies for calculating optimal tension based on material parameters and detail the detrimental effects of mismatched tension settings, including permanent yarn damage and product deformation. The research concludes that a deep understanding of material science is essential for optimizing the weaving process for any given yarn.